Analisis Determinan Kinerja Keuangan - Amaliah, Riska; Dahruji, Dahruji (Universitas Gorontalo, 2023)
The following research aims to find out what factors influenced the financial performance of Islamic Commercial Banks at OJK and BI during the Covid-19 pandemic for the 2019-2021 period. The analysis methodology is panel data regression with Eviews 12. The sample used is 12 BUS for the 2019-2021 period. The variables used are Operational Costs to Operating Income (BOPO), Non Performing Financing (NPF), Inflation, and Statutory Reserves (GWM). The results is all variables simultaneously had a significant influence on the financial performance of BUS, based on F test. Meanwhile, on t test, the BOPO and GWM variables are proven to have an influence on the financial performance of BUS. NPF and inflation had no effect in BUS financial performance (ROA). So that it can be concluded that BUS at OJK and BI in 2019-2021 during the Covid-19 pandemic could handle their financial performance quite well. Thereforethat must used to evaluation for BUS in order to improve operational performance. In order to avoid a decline in financial performance during the Covid-19 pandemic, BUS in OJK and BI are required to prioritize strategic steps to improve their financial performance and if there’s a problem with the process, it can be handled properly.